2020
DOI: 10.1021/jacs.9b11239
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Emergence of RNA from a Prebiotically Plausible Mixture of Ribonucleotides, Arabinonucleotides, and 2′-Deoxynucleotides

Abstract: The abiotic synthesis of ribonucleotides is thought to have been an essential step toward the emergence of the RNA world. However, it is likely that the prebiotic synthesis of ribonucleotides was accompanied by the simultaneous synthesis of arabinonucleotides, 2′-deoxyribonucleotides, and other variations on the canonical nucleotides. In order to understand how relatively homogeneous RNA could have emerged from such complex mixtures, we have examined the properties of arabinonucleotides and 2′-deoxyribonucleot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 57 publications
(121 reference statements)
0
63
0
1
Order By: Relevance
“…As previous reports suggest that nucleobase identity has little impact on the rate of formation of the imidazolium-bridged dinucleotide intermediate ( 25 , 26 ), we utilized 2AIptC as a model substrate, which allowed us to investigate intermediate formation at a much higher concentration. When we incubated purified 2AIptC at a concentration of 60 mM at pH 8 and followed the reaction by 31P-NMR, we found that the imidazolium-bridged TNA dinucleotide is formed, but the observed rate of 8.8 × 10 −4 h −1 mM −1 is approximately 4–5-fold slower than the corresponding rates for the activated ribonucleotides 2AI-rA and 2AI-rC (3.2 and 4.5 × 10 −3 h −1 mM −1 ) ( 26 , 27 ) (Figure 2D ). Nonenzymatic copying rates are dependent on multiple factors, including the rate of formation of imidazolium-bridged dinucleotide intermediates and their reactivities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous reports suggest that nucleobase identity has little impact on the rate of formation of the imidazolium-bridged dinucleotide intermediate ( 25 , 26 ), we utilized 2AIptC as a model substrate, which allowed us to investigate intermediate formation at a much higher concentration. When we incubated purified 2AIptC at a concentration of 60 mM at pH 8 and followed the reaction by 31P-NMR, we found that the imidazolium-bridged TNA dinucleotide is formed, but the observed rate of 8.8 × 10 −4 h −1 mM −1 is approximately 4–5-fold slower than the corresponding rates for the activated ribonucleotides 2AI-rA and 2AI-rC (3.2 and 4.5 × 10 −3 h −1 mM −1 ) ( 26 , 27 ) (Figure 2D ). Nonenzymatic copying rates are dependent on multiple factors, including the rate of formation of imidazolium-bridged dinucleotide intermediates and their reactivities.…”
Section: Resultsmentioning
confidence: 99%
“…The largest deviations between the two structures are at the primer terminus, where the tG residue is shifted and twisted compared to the native RNA primer, with distances in the range of 1.5–2.4 Å between the corresponding atoms of the threose and ribose sugar rings (Figure 6E ). The tG residue has a glycosidic linkage torsion χ angle of –121° (Table 1 ), compared to a typical χ angle of –168° for the ribonucleotides of the primer ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a water restricted environment such as the topmost layers of the air/ice interface, the bases would be more prone to base-stacking, enabling the correct base pairing with other free nucleotide that would be floating in the topmost part of the ice-QLL, where the water diffusivity is faster. 42 In addition, since the synthesis of building blocks for nucleotide synthesis has been shown to be plausible in prebiotic aqueous conditions, 14,[43][44] an immobilized and stretched out ssRNA on ice, as the one shown in Fig. 1b, could be more prone to polymerization and self-replication with free nucleotides diffusing in the ice-QLL than a compact arrangement in the absence of protein-assisted replicase.…”
Section: Discussionmentioning
confidence: 99%
“…11 Unresolved questions remain, however, about the emergence of prebiotic RNA and its evolution in the absence of protein-assisted biochemical mechanisms. Even granting abiotic formation of nucleotides in a prebiotic soup (a topic still intensely debated 6,[11][12][13][14], polymerization of nucleotides faces an uphill free energy gradient. 11 In addition, in aqueous solution at room temperature RNA polynucleotides degrade quickly 15 because the phosphodiester link between monomers is vulnerable to nucleophilic attack and breakage by the deprotonated 2'-OH group of the ribose sugar.…”
mentioning
confidence: 99%
“…The incorporation of an arabino-nucleotide into a growing oligonucleotide during primer extension is essentially a chain terminating event (Kim et al 2020). Such events would be fatal if genome replication required continuous end-to-end copying of a template strand.…”
Section: Replication Of the Virtual Circular Genomementioning
confidence: 99%